Added Value of a New Strain Elastography Technique in Conventional Ultrasound for the Diagnosis of Breast Masses: A Prospective Multicenter Study - Wei, Qi; Yan, Yu-Jing; Wu, Ge-Ge; Ye, Xi-Rong; Jiang, Fan; Liu, Jie; Wang, Gang; Wang, Yi; Wang, Yu; Pan, Zhi-Ping; Hu, Jin-Hua; Song, Juan; et al. (Frontiers in Oncology, 2021)
Objective: This study aimed at exploring the value of elasticity score (ES) and strain ratio (SR) combined with conventional ultrasound in distinguishing benign and malignant breast masses and reducing biopsy of BI-RADS (Breast Imaging Reporting and Data System) 4a lesions. Methods: This prospective, multi-center study included 910 patients from 9 different hospitals. The acquisition and analysis of conventional ultrasound and strain elastography (SE) were obtained by radiologists with more than 5 years of experience in breast ultrasound imaging. The diagnostic sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and area under curve (AUC) of conventional ultrasound alone and combined tests with ES and/or SR were calculated and compared. Results: The optimal cut-off value of SR for differentiating benign from malignant masses was 2.27, with a sensitivity of 60.2% and a specificity of 84.8%. When combined with ES and SR, the AUC of the new BI-RADS classification increased from 0.733 to 0.824 (p < 0.001); the specificity increased from 48.1% to 68.5% (p < 0.001) without the decreased of the sensitivity (98.5% vs 96.4%, p = 0.065); and the PPV increased from 52.2% to 63.7% (p < 0.001) without the loss in the NPV (98.2% vs 97.1%, p = 0.327). All three combinations of conventional ultrasound, ES and SR could reduce the biopsy rate of category 4a lesions without reducing the malignant rate of biopsy (from 100% to 68.3%, 34.9% and 50.4%, respectively, all p < 0.001). Conclusions: SE can be used as a useful and non-invasive additional method to improve the diagnostic performance of conventional ultrasound by increasing AUC and specificity, and reduce unnecessary biopsy of BI-RADS 4a lesions.